STUDY ON WALK-THROUGH ENERGY AUDIT OF A FACULTY BUILDING - Usman, Abdulyakin; Gadanya, Tukur Sani; Iliyasu, Abubakar Lawan (FUDMA JOURNAL OF SCIENCES, 2023)
Nigeria has been facing energy crisis for several years to meet the growing energy needs. Therefore, for sustainable environment and to contribute towards carbon neutrality, it is very much crucial to introduce energy audit in every sector in order to cut the growing demand. As such, this paper focuses on walk-through energy audit of Faculty of Engineering building in Federal University Dutsin-Ma. Data was collated manually and “Microsoft Excel” tool was used to analyze the building’s energy consumption. Electrical systems in the building were partitioned in to 68% for Surface panel light, 19% for Fan, 8% for AC, 3% for Fridge, 1% for Computer, 0.2% for projector, and 0.4% for printer and TV respectively. The result obtained shows total connected electric load as 131254-watt, with 10480-watt for lighting, 3380-watt for electrical equipment and 117394-watt for cooling and ventilation systems. Moreover, average individual energy consumption per day was found to be 463-kWh for AC, 151-kWh for Fan, 73-kWh for lighting, 23-kWh for fridge, 0.3-kWh for printer, 0.4-kWh for projector, 0.7-kWh for TV, and 10-kWh for Computer. The result also revealed that lighting systems have the highest percentage on number of appliances, whilst cooling and ventilation parameters have the highest power consumption amongst other parameters. Therefore, energy conservation measures discussed for AC being the highest energy consuming appliance may result to optimistic energy saving. Furthermore, reliable environmental-friendly alternative energy source that is up to 131-kW can be use to power lighting, cooling & ventilation and electrical appliances of the Faculty building.